Grade 3 metastatic neuroendocrine neoplasms of two unusual primary sites with contrasting differentiation characteristics: Dual tracer positron emission tomography and computed tomography imaging (18F-fluorodeoxyglucose and 68Ga-DOTATATE) correlates and their treatment implications - Loharkar, Sarvesh; Basu, Sandip (World Journal of Nuclear Medicine, 2021)
The correlates of dual tracer positron emission tomography and computed tomography (PET-CT) (18F-fluorodeoxyglucose [18F-FDG] and 68Ga-DOTATATE) in patients of Grade 3 neuroendocrine neoplasms (NENs) are presented. The first, a patient of gall bladder NEN, operated, with histopathology suggestive of high-grade well-differentiated neuroendocrine tumors with MiB-1 labeling index of 35%, showed uptake with both 18F-FDG and 68Ga-DOTATATE, including an uptake equivalent to Krenning score of 3–4 on 68Ga-DOTATATE PET-CT; in the second, a patient of esophageal NEN, Grade 3 with poor differentiation features, with MiB-1 labeling index of 70%, thereby qualifying for Grade 3 neuroendocrine carcinoma, the FDG uptake was high with minimal uptake on 68Ga-DOTATATE PET-CT. The illustrations reiterate the impression that relative uptake of 68Ga-DOTATATE/FDG in the NEN lesions forms a valuable parameter for assessing the dynamic tumor biology in continuum and thus personalizing the treatment strategies.
Keywords: 18F-fluorodeoxyglucose positron emission tomography and computed tomography; 68Ga-DOTATATE; dual tracer positron emission tomography and computed tomography; grade 3; Ki-67/MIB-1 labeling index; neuroendocrine neoplasms